Tingkat Kompetensi Petani Agribisnis Sayuran Pada Lahan Sempit di Kota Banda Aceh dan Kabupaten Aceh Besar - Muhibuddin Muhibuddin; Siti Amanah; Dwi Sadono (Jurnal Penyuluhan, 2015)
The research objectives are to analyze the level of agribusiness competencies of smallholders with vegetable planting, the correlated factors with agribusiness competence of smallholders with vegetable planting, and the strategies of increasing agribusiness competence of smallholders with vegetable planting. The respondents are vegetable farmers who live in the sub-district Syiah Kuala of Banda Aceh and sub-district Darussalam of Aceh Besar. Sampling was done by simple random sampling. Data collection was conducted on the 77 respondents using survey, interviews and observations technique, starting in April 2015 The descriptive analysis and correlation test (Pearson correlation) were used to analyze the data.The results showed that the level of agribusines competencies of smallholders with vegetable planting in Banda Aceh and Aceh Besar including moderate category. The moderate agribusiness competence is shown by the moderate level of knowledge, attitude, and skill. There is a very real correlation between: the characteristics of the socio-demographic (age, level of formal education, non-formal education, and experience), motivation to farm, interaction and communication of farmers with agribusiness competencies of smallholders with vegetable planting. The effective strategies that can improve the agribusiness competence of smallhoders are: improve training and field school for farmers, increase the interaction and communication of farmers with extension workers, and the development of farmers groups.Keyword: smallholders,vegetable planting, characteristics, agribusiness competencies